Nonprofit Sector and Part-Time Work: An Analysis of Employer-Employee Matched Data on Child Care Workers - Mocan, H. Naci; Tekin, Erdal (The Review of Economics and Statistics, 2003)
This paper uses a rich employer-employee matched data set to investigate the existence and the extent of nonprofit and part-time wage and compensation differentials in child care. The empirical strategy adjusts for workers' self-selection into the for-profit or the nonprofit sector and into full-time or part-time work, as well as for unobserved worker heterogeneity, using a discrete factor model. We find differences between the regimes (full-time for-profit, full-time nonprofit, part-time for-profit, part-time nonprofit) in the manner in which human capital characteristics of the workers are rewarded. There is substantial variation in wages as a function of employee characteristics, and there is variation in wages within sectors. The results indicate that part-time jobs are good jobs in center-based child care, and there exist nonprofit wage and compensation premia, which support the property-rights hypothesis.